Fizikalne lastnosti polimerov v farmaciji - ali jih poznamo? - Draksler, Petra (Farmacevtski vestnik, 2016)
The main components of matrix tablets are hy- drophilic polymers, which swell and form gels in contact with water and therefore control drug re- lease. Generally utilized polymers for this purpose are categorized as natural (xanthan), synthetic (poly- ethylene oxide) and semi-synthetic (hydroxypropyl- methylcellulose). Understanding of their physico- chemical characteristics and variability such as molecular weight, viscosity, type of substitute and degree of substitution, critical polymer concentration as well as size and shape of polymer chain are es- sential for formulation of robust tablets with desired release kinetics. In this review, the most important physico-chemical properties for formulation of ma- trix tablets are elaborated at examples of hydrox- ypropylmethylcellulose, polyethylene oxide and xan- than.
Keywords: farmacevtski pripravki; fizikalno kemijske lastnosti; HPMC; ksantan; naravni polimeri; ogrodne tablete; tablete